Assessment of Oxygen Saturation and Hematological Changes in Canine Undergoing Castration Surgery Under General Anesthesia (Indian Journal of Animal Production and Management, 2026)
Background: Castration under general anesthesia is clinically meaningful,  but there are potential physiological risks related to respiratory function and  hematological stability. Only with a better understanding of these effects can  anesthetic protocols be refined for optimal surgical outcomes. Aims: This study explores the physiological impact of general anesthesia on  peripheral oxygen saturation (SpO₂) and hematological parameters in male  dogs undergoing elective castration at three time points: pre- (baseline),  during (mid-surgery), and post (recovery) anesthesia. Results: Oxygen saturation declined significantly during anesthesia (86.16  ± 4.67 %) compared with baseline (99.00 ± 0.00 %) and partially recovered  post-anesthesia (95.83 ± 1.70 %) (P ≤ 0.01). Hematological analysis showed  postoperative leukocytosis (WBC: 21.84 ± 5.94 × 10³/μL) and significant  reductions in red blood cell count (8.17 ± 0.52 × 10⁶/μL), hemoglobin (9.45  ± 0.61 g/dL), and hematocrit (31.55 ± 3.36 %) compared with baseline (P  ≤ 0.05–0.01). Red cell distribution width (RDW) and platelet distribution  width (PDW) increased, whereas platelet count decreased, likely reflecting  stress and hemodilution responses to anesthesia and surgery. Conclusion: General anesthesia during canine castration induces transient  hypoxemia and distinct hematological alterations. Therefore, continuous  perioperative respiratory monitoring and tailored anesthetic management  are recommended to enhance recovery and minimize complications. These  findings may assist veterinarians in refining anesthetic monitoring protocols  for safer routine castration procedures. Further research with larger  populations is needed to validate these observations and assess long-term  physiological outcomes.
Keywords: anesthesia, ketamine-xylazine, oxygen saturation, hematological changes, castration, hypoxemia, surgery.